Kemampuan Pematematikaan Horizontal Siswa Sekolah Dasar dalam Menyelesaikan Masalah Bilangan Bulat Positif - Najwa, Wulida Arina; Susiswo, Susiswo; As’ari, Abdur Rahman (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: One of the mathematisation processes in Realistic Mathematics Education is horizontal mathematisation. Using a qualitative approach, this research describes the horizontal mathematisation ability of grade 4 elementary school students in solving problem-solving questions on positive integers. The result of this research shows that there is a relationship between students' mathematical abilities and their horizontal mathematisation abilities. Students with moderate ability levels have moderate horizontal mathematisation abilities and students with high levels of ability have high horizontal mathematisation abilities.Abstrak: Salah satu proses matematisasi dalam Realistic Mathematics Education adalah pematematikaan horizontal. Penelitian ini menggunakan pendekatan kualitatif yang mendeskripsikan kemampuan pematematikaan horizontal siswa kelas IV sekolah dasar dalam menyelesaikan soal pemecahan masalah bilangan bulat positif. Hasil penelitian ini menunjukkan bahwa ada hubungan antara kemampuan matematika siswa dengan kemampuan pematematikaan horizontal siswa. Siswa pada tingkat kemampuan rendah memiliki kemampuan pematematikaan horizontal yang rendah, sedangkan siswa pada tingkat kemampuan tinggi memiliki kemampuan pematematikaan horizontal yang tinggi.